The Practice of Money Politics in Village Head Elections and Its Effect on The Participation Level of Beginner Voters - Effendi Hasan; Aminah Aminah; Haji Jamaie Haji Hamil; Mukhrijal Mukhrijal (Universitas Muhammadiyah Yogyakarta, 2023)
This study investigates the prevalence of money politics in village head elections in Gampong Gunong Meulinteung and its impact on novice voter participation. General elections are crucial to democracy, but they are often undermined by electoral fraud, particularly money politics, which seeks to sway voters through monetary and material incentives. Employing a descriptive quantitative method, data were collected through questionnaires and interviews, with statistical analysis conducted using SPSS. Results indicated that money politics manifested as money (76%), goods (57%), and services (58%) offered to voters. Correlation analysis revealed a modest influence of money politics on novice voters at 7.6%, while 92.4% based their choices on factors such as age, education, and candidate personality. This research enhances the understanding of the relationship between money politics and voter behavior, particularly among novice voters, an area where empirical data is scarce. The study’s focus on the impact of money politics on first-time voters in village head elections offers fresh insights into electoral fraud at the local governance level, especially in rural Indonesia. Emphasizing the notable yet limited impact of money politics, this research underscores the necessity of providing political education to novice voters and advocates for the establishment of village-level task forces to address electoral fraud, ultimately aiming to enhance the integrity of local democratic processes.